Is tinnitus an early voice of masked hypertension? High masked hypertension rate in patients with tinnitus. (3rd April 2019) - Gun, Taylan; Özkan, Selçuk; Yavuz, Bunyamin
ABSTRACT: Objectives : Tinnitus is hearing a sound without any external acoustic stimulus. There are some clues of hypertension can cause tinnitus in different ways. The aim of the study was to evaluate the relationship between tinnitus and masked hypertension including echocardiographic parameters and severity of tinnitus. Methods : This study included 88 patients with tinnitus of at least 3 months duration and 85 age and gender-matched control subjects. Tinnitus severity index was used to classify the patients with tinnitus. After a complete medical history, all subjects underwent routine laboratory examination, office blood pressure measurement, hearing tests and ambulatory blood pressure monitoring. Masked hypertension is defined as normal office blood pressure measurement and high ambulatory blood pressure level. Results : Baseline characteristics in patients and controls were similar. Prevalence of masked hypertension was significantly higher in patients with tinnitus than controls (18.2% vs 3.5%, p = 0.002). Office diastolic BP (76 ± 8.1 vs. 72.74 ± 8.68, p = 0.01), ambulatory 24-H diastolic BP (70.2 ± 9.6 vs. 66.9 ± 6.1, p = 0.07) and ambulatory daytime diastolic BP (73.7 ± 9.5 vs. 71.1 ± 6.2, p = 0.03) was significantly higher in patients with tinnitus than control group. Tinnitus severity index in patients without masked hypertension was 0 and tinnitus severity index in patients with masked hypertension were 2 (1–5). Conclusion : This study demonstrated that masked hypertension must be kept in mind if there is a complaint of tinnitus without any other obvious reason.